Creation of a Virtual Nutrition Support Team to Improve Quality of Care for Patients Receiving Parenteral Nutrition in a Multisite Healthcare System. (25th July 2019) - Meyer, Michelle; Hartwell, Jennifer; Beatty, Amy; Cattell, Theresa
Abstract: Background: Parenteral nutrition (PN) is a complicated therapy in which having specially trained clinicians can provide benefit, but it can be difficult to provide this level of expertise to all patients requiring PN. Creation of a virtual nutrition support team (NST) model allows patients across multiple hospitals to receive care from NST clinicians using remote conferencing technology on a daily basis. This study reviewed retrospective data from before and after implementation of the virtual model to assess quality indicators. Methods: The NST was developed including a team of dietitians and pharmacists with a physician medical director. Practice guidelines were developed to provide consistent methods for ordering and monitoring patients receiving PN. Patient charts in both the preintervention and postintervention groups were reviewed for indication for PN, duration of therapy, blood glucose levels, and demographic data. Results: A greater proportion of patients in the postintervention period had appropriate orders (97.2%) compared with patients in the preintervention period (58.9%) ( P  < 0.001). A greater proportion of patients in the postintervention period had blood glucose levels within the range 65–180 mg/dL (83.5%) compared with patients in the preintervention period (62.2%) ( P <  0.001). Conclusion: A virtual team model was applied to remotely manage patients receiving PN in a large healthcare system. This resulted in optimized care of patients by reducing inappropriately prescribed therapy and improving blood glucose control.